BAGAIMANA SELF-COMPASSION MEMODERASI PENGARUH MEDIA SOSIAL TERHADAP KETIDAKPUASAN TUBUH? - Marizka, Diba Shabrina; Maslihah, Sri; Wulandari, Anastasia (JURNAL PSIKOLOGI INSIGHT, 2019)
This research aims to determine the influence of intensity of social media use to body dissatisfaction moderated by self-compassion among early adulthood. This research used quantitative research method with 403 early adulthood participated in this research. Instruments used were Intensitas Penggunaan Media Sosial (IPMS) to measure intensity of social media use, Multiple Body-Self Related Questionnaire Appearance Scales (MBSRQAS) to measure body dissatisfaction, and Self-Compassion Scale (SCS) to measure selfcompassion. The analysis technique used is Moderated Regression Analysis (MRA). Result show that intensity of social media use influences body dissatisfaction with a significance value 0.006. Self-compassion influences body dissatisfaction with significance value 0.000. Self-compassion moderated the influence of intensity of social media use on body dissatisfaction with significance value 0.000.